2018
DOI: 10.3390/jcm7050104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Oral Pyridostigmine on the Ileus after Abdominal Surgery: A Blinded Randomized Clinical Trial

Abstract: Postoperative ileus is one of the most important and common complications after abdominal surgery. This single-blind randomized clinical trial study was conducted with the aim of evaluating the effect of oral pyridostigmine (60 mg) on the duration and frequency of response to the treatment of ileus after abdominal surgery on 40 patients in two 20-subject groups of oral pyridostigmine (interventional) and starch (control) in 2015. All 40 people completed the study process and entered the final analysis. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 34 publications
(39 reference statements)
0
21
0
Order By: Relevance
“…Thus, pyridostigmine is shown to reduce constipation in patients with Parkinson's disease and autoimmune neuropathy 14 , as well as in other patients with refractory chronic constipation 15 . Furthermore, one study has shown that oral pyridostigmine is an effective and safe treatment for postoperative ileus 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pyridostigmine is shown to reduce constipation in patients with Parkinson's disease and autoimmune neuropathy 14 , as well as in other patients with refractory chronic constipation 15 . Furthermore, one study has shown that oral pyridostigmine is an effective and safe treatment for postoperative ileus 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, given the low sample size, this study was underpowered. 40 This study had a greater proportion of caesarean section patients, and limitations of sample bias. In addition, colorectal operations that have the highest incidence of POI were not included, and the routine use of nasogastric tubes likely confounded the results (as this is not standard practice in the types of surgery included in the study).…”
Section: Pyridostigmine For Poimentioning
confidence: 95%
“…In the first 24 h, more patients given pyridostigmine passed stool compared to the placebo group (95% versus 50%, p = 0.001). However, given the low sample size, this study was underpowered 40 . This study had a greater proportion of caesarean section patients, and limitations of sample bias.…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 97%
“…Median age was 58 (50-82) years and seven (47%) were men. Most participants had an ASA grade ≥2 (53%), and the median BMI was 27 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) kg/m 2 . Benign conditions such as reversal of stoma and diverticulosis were the most common indication for surgery (n = 8, 53%), and 53% of procedures were minimally invasive (Table 1).…”
Section: Re Sultsmentioning
confidence: 99%
“…Although there have been some concerns regarding the use of neostigmine in the postoperative setting due to potential cardiac and respiratory side effects and a requirement for intensive monitoring, oral pyridostigmine is much safer in this regard and may be a good therapeutic option. In a randomized controlled trial (RCT) conducted by Maleknejad et al in patients undergoing abdominal surgery [25], the safety and efficacy data appeared promising, with a 1‐day reduction in time to first passage of stool and flatus and no obvious adverse effects. However, in that study all patients underwent noncolorectal abdominal surgery, with a lower baseline risk of ileus and a lower risk of cardiorespiratory complications.…”
Section: Introductionmentioning
confidence: 99%